Exploring Inflectional Morphemes in Sentences Written by EFL Students - Artika; Bochari, Siska; Lebagi, Desrin; Maf'ulah (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
The objective of this research was to find out the types of inflectional morphemes that the students frequently misused and to find out the difficulty factors faced by students in using the type of inflectional morphemes. The population of this research consisted of 5th-semester students from the English Education Study Program at Tadulako University. The sample was selected using a simple random sampling technique, and there were 136 students in the 5th-semester class. The method of this research depends on the quantitative descriptive data using statistical analysis. Tests and questionnaires were used to collect the data. The researchers found that the ablaut adjective as an irregular form is the type of inflectional morphemes frequently misused by the students; the frequency of many incorrect forms is 160, and the difficulty factors that are affecting the students' use of inflectional morphemes are psychological as internal factors and peer and advisor support as the external factors.